2018
DOI: 10.1128/aac.01396-17
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Treatment and Clinical Outcomes among Patients with Methicillin-Susceptible Staphylococcus aureus Bloodstream Isolates Possessing Detectable mecA by a Commercial PCR Assay Compared to Patients with Methicillin-Resistant Staphylococcus aureus Bloodstream Isolates

Abstract: -positive isolates phenotypically susceptible to cefoxitin (-methicillin-sensitive [MSSA]) have been identified. We describe the treatment and outcomes among patients with-MSSA bloodstream infections (BSI) and MRSA BSI matched 1:1 for age, BSI origin, and BSI type ( = 17 per group). Compared to MRSA BSI patients, -MSSA BSI patients more often experienced clinical failure (58.8% and 11.8%, = 0.010), driven largely by persistent bacteremia (35.3% and 11.8%). -MSSA BSI patients may be at higher risk for poor clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The use of molecular microbial genotypic assays to predict antimicrobial susceptibility in bacteria and guide clinical practice is not new and has been applied in Mycobacterium tuberculosis infections [22], Staphylococcus aureus infections [23], and more recently, Enterobacteriaceae [24]. However, there are very few prospective studies using molecular methods to predict antimicrobial susceptibility along with clinical outcomes and none using these methods in the context of increasingly antimicrobial resistant N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular microbial genotypic assays to predict antimicrobial susceptibility in bacteria and guide clinical practice is not new and has been applied in Mycobacterium tuberculosis infections [22], Staphylococcus aureus infections [23], and more recently, Enterobacteriaceae [24]. However, there are very few prospective studies using molecular methods to predict antimicrobial susceptibility along with clinical outcomes and none using these methods in the context of increasingly antimicrobial resistant N. gonorrhoeae.…”
Section: Discussionmentioning
confidence: 99%
“… S. aureus strains which are phenotypically methicillin susceptible but contain the mecA gene have been reported to have a higher risk of persistent bacteraemia, even when treated with vancomycin [80]. AMR elements have been implicated as virulence determinants in another Gram-positive species; Streptococcus pneumoniae , where a PBP variant associated with penicillin tolerance (though not resistance) was associated with meningitis among isolates found in invasive pneumococcal disease [81].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of SAB over 21 years in the USA showed that within CC-8, the MRSA lineage USA300 was associated with higher rates of metastatic infection compared to the rest of the spa -t008 complex after adjusting for patient and clinical variables [ 79 ]. S. aureus strains which are phenotypically methicillin susceptible but contain the mecA gene have been reported to have a higher risk of persistent bacteraemia, even when treated with vancomycin [ 80 ]. AMR elements have been implicated as virulence determinants in another Gram-positive species; Streptococcus pneumoniae , where a PBP variant associated with penicillin tolerance (though not resistance) was associated with meningitis among isolates found in invasive pneumococcal disease [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…73 S. aureus strains which are phenotypically methicillin susceptible but contain the mecA gene have been reported to have a higher risk of persistent bacteraemia, even when treated with vancomycin. 74 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint Overall, we found MRSA was more prevalent in bacteraemia than carriage in samples, when sampling the population representatively. In the UK at this time MRSA was almost exclusively healthcare associated.…”
Section: Discussionmentioning
confidence: 75%
“…73 S. aureus strains which are phenotypically methicillin susceptible but contain the mecA gene have been reported to have a higher risk of persistent bacteraemia, even when treated with vancomycin. 74 AMR elements have been implicated as virulence determinants in another Gram positive species; Streptococcus pneumoniae , where a PBP variant associated with penicillin tolerance (though not resistance) was associated with meningitis among isolates found in invasive pneumococcal disease. 75…”
Section: Discussionmentioning
confidence: 99%